PENGGUNAAN MEDIA SOSIAL DENGAN PENDEKATAN MODEL AIDA BAGI ROTI BUND DALAM MENINGKATKAN MINAT BELI KONSUMEN - Bunga Ega Evania; Roni Kastaman; Totok Pujianto (Universitas Galuh, 2022)
The internet offers many benefits for small and medium businesses to increase the marketing of their products. One of the rapidly developing internet technologies that have the potential to encourage small and medium business marketing is social media. Roti Bund must improve its marketing strategy using social media so that it attracts consumer buying interest. This study aims to determine whether there is a positive and significant influence between the Marketing Strategy through Social Media